Pengaruh Kepemimpinan, Kecerdasan Emosional terhadap Kinerja Pegawai dengan Disiplin Kerja Sebagai Variabel Intervening pada Badan Penanggulangan Bencana Daerah (BPBD) - Sari, Fajar; Iba, Zainuddin; Simahatie, Mai (Singkite Journal, 2025)
The purpose of the study was to analyze the influence of factors that affect the performance of employees of the Bireuen Regency Regional Disaster Management Agency. By determining the leadership factor, emotional intelligence and work discipline as intervening variables. The research was descriptive and verification, with the data analysis method used to test the hypothesis was path analysis using the latest SPSS version 26. The results of the path analysis showed, (1) leadership affects employee performance, (2) emotional intelligence affects employee performance, (3) leadership and emotional intelligence simultaneously affect employee performance by 44.5%. (4) Work discipline as an intervening variable that affects leadership and emotional intelligence on employee performance